2015 12th International Conference on Service Systems and Service Management (ICSSSM) 2015
DOI: 10.1109/icsssm.2015.7170278
|View full text |Cite
|
Sign up to set email alerts
|

An applied case of quadratic assignment problem in hospital department layout

Abstract: This paper discusses the la functional departments in the hospital. B departments overall, we aim to minimize the time for the outpatients from the registry t departments, thus enhancing the hospital's Actually, this is typically a quadratic assignmen Since the hospital's departments tend to vary presents a way of combining the small spaces department and dividing the large spaces to loc smaller department. Then, as a variant assignment problem, an Integer Programming to solve this layout problem. Finally, To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Authors indicated that the QAP can be used for layout optimization (Burkard, Çela, Pardalos, & Pitsoulis, 1998; Loiola, Abreu, & Boaventura-Netto, 2004). Many provided solutions for QAP through heuristics (Elshafei, 1977; Helber, Böhme, Oucherif, Lagershausen, & Kasper, 2016; Silva, Resende, Pardalos, Mateus, & De Tomi, 2013; Yeh, 2006) and linear, nonlinear, or mixed optimizations (Chraibi, Kharraja, Osman, & Elbeqqali, 2015; Feng & Su, 2015; Hahn & Krarup, 2001; Murtagh, Jefferson, & Sornprasit, 1982; Nickel, 2000). Other modeling approaches were used by authors such as Chraibi, Kharraja, Osman, and Elbeqqali (2016) and Abbasi, Ahmadi, Naderi, and Vahdami (2017) for layout planning.…”
Section: Resultsmentioning
confidence: 99%
“…Authors indicated that the QAP can be used for layout optimization (Burkard, Çela, Pardalos, & Pitsoulis, 1998; Loiola, Abreu, & Boaventura-Netto, 2004). Many provided solutions for QAP through heuristics (Elshafei, 1977; Helber, Böhme, Oucherif, Lagershausen, & Kasper, 2016; Silva, Resende, Pardalos, Mateus, & De Tomi, 2013; Yeh, 2006) and linear, nonlinear, or mixed optimizations (Chraibi, Kharraja, Osman, & Elbeqqali, 2015; Feng & Su, 2015; Hahn & Krarup, 2001; Murtagh, Jefferson, & Sornprasit, 1982; Nickel, 2000). Other modeling approaches were used by authors such as Chraibi, Kharraja, Osman, and Elbeqqali (2016) and Abbasi, Ahmadi, Naderi, and Vahdami (2017) for layout planning.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, several item pairs must be placed within a given distance when severe timing constraints are imposed on them in FPGA design. Furthermore, it also contributes to job assignment problems and relocating the departments in companies [19], [20]. In practice, to maximize work efficiency, several staffs and departments should be close.…”
Section: Constrained Slot Placement Problemmentioning
confidence: 99%
“…However, the papers which apply QAP formulation to a service sector problem are very limited (Saremi et al, 2008). One of the studies that is applied on service sector considers the patient rotation in hospital by utilizing QAP (Feng and Su, 2015). Patient rotation is modeled as integer programing and results demonstrates the 11.55% decrease in average walking time for Tongji Hospital.…”
Section: Introductionmentioning
confidence: 99%